Explaining foreign holdings of Asia's debt securities: The Feldstein-Horioka paradox revisited - Charles Yuji Horioka; Akiko Terada-Hagiwara; Takaaki Nomoto (Osaka University, Institute of Social and Economic Research (ISER), 2015)
In this paper, we find that home bias is still present in all economies and regions, especially in the case of short-term debt securities, but that there are substantial variations among economies and regions in the strength of home bias, with the Eurozone economies, the US, and developing Asia showing relatively weak home bias and advanced Asia, especially Japan, showing relatively strong home bias. We then examine trends over time in foreign holdings of debt securities and find that capital has been flowing from the US and the Eurozone economies to both advanced Asia (especially Japan) and developing Asia and that foreign holdings of debt securities have been increasing in advanced as well as developing Asia but for different reasons. The main reason in the case of advanced Asia (especially Japan) appears to be higher riskadjusted returns, whereas the main reason in the case of developing Asia appears to be the growth of debt securities markets combined with relatively weak home bias and (in the case of short-term securities) lower exchange rate volatility. Finally, we find that since the Global Financial Crisis, foreign holdings of debt securities have declined (i.e., that home bias has strengthened) in all economies and regions except developing Asia, where they have increased (except for a temporary decline in 2008) but where their share is still much lower than the optimal share warranted by the capital asset pricing market model.
Keywords: F21; F32; F34; F65; G01; G15; O53; 330; capital asset pricing model; cross-border portfolio investments; debt securities; Feldstein-Horioka paradox; Feldstein-Horioka puzzle; foreign debt holdings; Global Financial Crisis; government bonds; government securities; home bias; international capital flows; international capital mobility; international capital movements; safe haven; short-term capital movements; advanced Asia; developed Asia; developing Asia; non-Japan Asia; Eurozone; Japan